The commanding heights : - Yergin, Daniel (Simon & Schuster, 1998)
The Pulitzer Prize-winning author of The Prize joins a leading expert on the global market place to present an incisive overview of the risks and opportunities that are emerging as the balance of economic power shifts around the world between government and markets.